2018
DOI: 10.5688/ajpe6806
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the Pharmacist-Patient Covenant

Abstract: The first tenet of the Code of Ethics for Pharmacists of the American Pharmacists Association describes the relationship between the pharmacist and the patient as a covenant. The central argument of this commentary is that the symbolic language of covenant, the metaphor used to describe the pharmacistpatient relationship, should be formally acknowledged as an ideal theory or concept. However, before committing to this ideal, there should be resonance with the realities of pharmacy practice. This commentary arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Building a committed relationship cannot occur at a distance. The pharmacist-patient relationship has changed over the past 30 years from one in which pharmacists focused solely on filling prescriptions without questioning a physician's order to one in which pharmacists recommend drug therapy to prescribers and offer personalized advice to patients on how to maximize the benefits of their medication [ 25 ]. In addition, by its very nature, pharmaceutical care is an iterative and ongoing process, as long as the patient has unresolved medication-related problems.…”
Section: Introductionmentioning
confidence: 99%
“…Building a committed relationship cannot occur at a distance. The pharmacist-patient relationship has changed over the past 30 years from one in which pharmacists focused solely on filling prescriptions without questioning a physician's order to one in which pharmacists recommend drug therapy to prescribers and offer personalized advice to patients on how to maximize the benefits of their medication [ 25 ]. In addition, by its very nature, pharmaceutical care is an iterative and ongoing process, as long as the patient has unresolved medication-related problems.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the hospital pharmacists play an increasingly important role in improving medication adherence, the role of which includes assessing medication adherence, identifying predisposing factors, providing consultations, and recommending targeted medication adherence strategies. The patients' medication adherence is inevitably correlated with the performance of pharmacists, 5,6 while it may also be dominated by their own social and psychological factors. Some pharmacists fail to fulfill the responsibilities expected by patients, resulting in patients' dissatisfaction with the attitude and behavior of pharmacists in pharmaceutical service, which may exert an adverse effect on the medication adherence of patients.…”
Section: Introductionmentioning
confidence: 99%
“…48 However, once pharmacists enter the profession, the current community practice environment may present significant barriers to achieving the ideals of code-postulated covenantal relationships. 49 The barriers may include frequently incomplete patient information, absence of time and privacy, and patients’ misunderstanding of pharmacist’s expertise—all coupled with a multitude of time-consuming demands on the pharmacist’s time from prescribers, insurers, manufacturers, and regulators. 49 A rare pharmacist practicing in a high-paced chain community pharmacy setting can acknowledge that they achieve ideal pharmacist-patient covenantal relationships with every patient.…”
Section: Data Synthesismentioning
confidence: 99%
“…49 The barriers may include frequently incomplete patient information, absence of time and privacy, and patients’ misunderstanding of pharmacist’s expertise—all coupled with a multitude of time-consuming demands on the pharmacist’s time from prescribers, insurers, manufacturers, and regulators. 49 A rare pharmacist practicing in a high-paced chain community pharmacy setting can acknowledge that they achieve ideal pharmacist-patient covenantal relationships with every patient. Besides, a recent study in Canada examining professional self-identification of pharmacists found that, unlike physicians, when pharmacists were patients or caregivers to the family members, they rarely disclosed their professional backgrounds or attempted to actively participate in and discuss the care being provided.…”
Section: Data Synthesismentioning
confidence: 99%